Acrodermatitis Chronica Atrophicans Coexisting with Lichen Sclerosus - Nowowiejska-Purpurowicz, Julia; Baran, Anna; Flisiak, Iwona (Dermatology Review/Przegląd Dermatologiczny, 2025)
A 38-year-old woman was admitted to the Department of Dermatology due to purple-pinkish macules observed on the thighs and buttocks, which were very firm on palpation. There were also several white-silverish papules on the knees and a patch on the buttock present. The IgM and IgG antibodies against Borrelia were both positive in ELISA, confirmed in western blot examination. Skin biopsy taken from the hardened lesions was suggestive of acrodermatitis chronica atrophicans, the second taken from the white papules was consistent with lichen sclerosus. The patient was consulted by the infectious diseases specialist who introduced doxycycline with significant improvement. We found only a few cases of acrodermatitis chronica atrophicans and lichen sclerosus coexistence. In the other cases, lichen sclerosus occurred at different body sites, in the genital or extragenital region. Physicians must be aware of the late manifestations of Lyme disease and consider it in the differential diagnosis despite the lack of tick bite history.